EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TS-TS) DAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION (TAI) TERHADAP HASIL BELAJAR MATEMATIKA - Monif Maulana; Nur Arina Hidayati (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
SMP Muhammadiyah 7 Yogyakarta is one of the schools that are low math achievement. The learning model that teachers use unvaried and learning process is teacher-centered. This study aimed to campare the cooperative Learning Two Stay Two Stray (TS-TS) model and cooperative learning Team Assisted Individualization (TAI) model in mathematics outcomes in even semester of seventh grade student in smp muhammadiyah 7 yogyakarta academic year of 2016/2017. The population in this study was seventh grade students consisting of 7 calsses. The sampling technique use random sampling technique that was by lottery class. From raffle earned that grade VII G class as TS-TS class and VII F Class as TAI class. Mathematics learning outcomes data obtained using the test method in the form of objective questions. Analysis of the data used one tailed t-test and two tailed t-test. From the test results obtained by the two tailed t-test  = 1,9180 and  = 1,5409, it means  >  with a significance level of 5% and 54 degrees of freedom, which means  was rejected. This suggest that there were differences in mathematics achievement between students who use cooperative model of TS-TS dan cooperative model of TAI. One tailed t-test result obtained that  = 1,9180 and  = 1,5409, it means  >  with a significance level of 5% and 54 degrees of freedom, which means  was rejected. This suggest that the learning outcomes of students who use the cooperative model of TS-TS was better than learning outcomes of students who use the cooperative model of TAI in even semester of seventh grade student in smp muhammadiyah 7 yogyakarta academic year of 2016/2017. Keywords: Effectiveness, Two Stay Two Stray, Team Assisted Individualization, Learning Outcomes